Education on the Nutritional Value and Diversification of Processed Products of Marus Tubers (Garut) in Kelebuh Village, Central Lombok - Ahmad Hardyan Isnaini; Auliya Supiani; Devia Rizki; Abdul Syafiq Syawal; Nur Nayna Ningsih; Novi Rahmawati; Chantika Nur Azizah; Rian; Indra Sopiandi; Kartika Indah Lestari; Nihla Farida (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2026)
Kelebuh Village has abundant local food resource potential in the form of arrowroot tubers (marus), but its utilization is still limited to traditional processing, resulting in low economic value and short shelf life. This community service activity aims to provide comprehensive education regarding the nutritional value of arrowroot as a functional food and introduce flour processing technology and its product diversification. The implementation method was carried out through four main stages: preparation, nutritional counseling by Batunyala Health Center experts, education on flour processing technology, and organoleptic testing of innovative products. The results of the activity showed that through nutritional counseling, the community successfully increased literacy regarding the benefits of dietary fiber and the low glycemic index of arrowroot for digestive health and prevention of degenerative diseases. During the technology education stage, the community mastered the technical skills of transforming fresh tubers into flour through slicing, hygienic drying, and milling processes to extend the shelf life of the raw material. Diversified products in the form of Marus Brownies and Marus Porridge received positive responses through organoleptic tests, with an acceptance rate of 95% in the taste aspect. This activity is expected to encourage food independence and become a pioneer for culinary businesses based on local wisdom in Kelebuh Village.